2018
DOI: 10.5021/ad.2018.30.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of O6-Methylguanine-DNA Methyltransferase Promoter Methylation in Patients with Melanoma: A Systematic Meta-Analysis

Abstract: Tumor suppressor gene O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation has been reported in melanoma. However, the clinical and prognostic significance of MGMT promoter methylation in patients with melanoma remained to be determined. A systematic search was performed to identify eligible papers published. The overall odds ratios (ORs) or hazard ratios and their 95% confidence intervals were calculated. Final 12 eligible publications involving Caucasian population were performed in this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A recent systemic meta‐analysis of 12 studies by Qi et al . noted that MGMT promoter methylation was higher in both primary MM and metastatic MM compared to normal controls 28 . Notably, they also found a higher incidence of MGMT promoter methylation in metastatic MM in blood samples compared to tissue samples, suggesting that MGMT promoter methylation could potentially be used as a biomarker for metastatic MM in blood samples 28 …”
Section: Discussionmentioning
confidence: 99%
“…A recent systemic meta‐analysis of 12 studies by Qi et al . noted that MGMT promoter methylation was higher in both primary MM and metastatic MM compared to normal controls 28 . Notably, they also found a higher incidence of MGMT promoter methylation in metastatic MM in blood samples compared to tissue samples, suggesting that MGMT promoter methylation could potentially be used as a biomarker for metastatic MM in blood samples 28 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MGMT hypermethylation is associated with an increased risk of NSCLC [8]. MGMT promoter methylation is also associated with the occurrence and invasion of melanoma [9]. Furthermore, MGMT methylation can also be used as a biomarker to predict carcinogenesis in a variety of tumors [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…O 6 -methylguanine-DNA methyltransferase (MGMT) is a widely studied specific DNA damage reversal repair protein that protects chromosomes from mutation, carcinogenesis, and cytotoxic effects of alkylating agents [7]. In previous studies, MGMT status was shown to be related to the occurrence and invasion of non-small cell lung cancer (NSCLC) [8], melanoma [9], malignant glioma [10], esophageal cancer [11], and prostate cancer [12]. MGMT also affected the chemotherapeutic effect of different tumor patients, but the results are controversial [8,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Because DNA methylation can inhibit transcription, methylation of MGMT promoter increases sensitivity to alkylating agents (27). Several studies have shown that methylation of MGMT promoter can predict whether alkylating agents can be of benefit in glioblastoma and low-grade gliomas (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Two other clinical trials have revealed that methylation status of MGMT promoter can predict the prognosis of glioma patients.…”
Section: The Prediction and Prognostic Value Of Mgmt Promoter Status mentioning
confidence: 99%